Examining challenges to Parental Involvement in Enhancing Academic Performance Among Grade 7 Learners/Students - Chissano, Amelia; Maseko, Nonhlanhla (Central European Journal of Educational Research, 2025)
Parental involvement is a critical determining factor of learners’ academic success, particularly during transitional educational phases such as Grade 7. This study explores the factors challenging parental engagement in supporting their children’s academic performance at this crucial stage in South Africa, Tshwane South District. Although extensive research has been conducted on parental involvement, there is limited studies focusing on the transitional phase of grade 7 within the South African context. Employing a qualitative approach, and purposively selected 11 participants (6 parents, 5 educators). Furthermore, data were collected through interviews, focus group discussions and document analysis. Findings indicate that socioeconomic constraints, limited parental education, communication gaps between schools and families, and parents’ time constraints significantly hinder effective involvement. Additionally, cultural perceptions of parental roles in education and students’ increasing need for autonomy in adolescence further complicate engagement efforts. The study also identifies systemic barriers, such as inadequate school initiatives to foster parent-teacher collaboration. Recommendations include capacity-building workshops for parents, and the development of inclusive communication strategies by schools. This paper highlights the need for a holistic, community-driven approach to overcoming barriers and fostering sustained parental involvement to enhance student achievement in Grade 7, offering insights that are particularly relevant within South African context.